Effect of Anti-inflammatory Drug Therapy on Clearance of 133Xe from Knee Joints of Patients with Rheumatoid Arthritis. Issue 5665 (2nd August 1969) - Dick, C.; Dick, P. H.; Nuki, G.; Whaley, K.; Boyle, J. A.; Shenkin, A.; Downie, W. W.; Buchanan, W. W.
Abstract : The degree of joint inflammation in 13 patients with rheumatoid arthritis, as measured by clinical indices, was reduced by both sodium salicylate and indomethacin. The clearance rate of 133 Xe was reduced by indomethacin alone, and showed no correlation with the clinical features.